2010
DOI: 10.4049/jimmunol.0902673
|View full text |Cite
|
Sign up to set email alerts
|

Human Eosinophils Recognize Endogenous Danger Signal Crystalline Uric Acid and Produce Proinflammatory Cytokines Mediated by Autocrine ATP

Abstract: Eosinophils are multifunctional leukocytes involved in various inflammatory processes, as well as tissue remodeling and immunoregulation. During inflammation and infection, injured cells and damaged tissues release uric acid and monosodium urate (MSU) crystals as important endogenous danger signals. Uric acid is also implicated in the immunogenic effects of an authentic Th2 adjuvant, aluminum hydroxide. Eosinophils often localize at sites of Th2-type chronic inflammation; therefore, we hypothesized that eosino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 60 publications
3
75
1
1
Order By: Relevance
“…31 Some studies have demonstrated that uric acid crystals can induce human eosinophils and neutrophils to produce the neutrophil chemokine CXCL8. 32,33 To examine whether uric acid crystals also modulate the expression of chemokines in FLS, we found that monosodium urate crystals were able to significantly increase the release of the chemokine CXCL8 from both control FLS and RA-FLS (P,0.05). Combined treatment of monosodium urate crystals with TNF-a or IL-1b resulted in the synergistic production of CXCL8 from control FLS (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…31 Some studies have demonstrated that uric acid crystals can induce human eosinophils and neutrophils to produce the neutrophil chemokine CXCL8. 32,33 To examine whether uric acid crystals also modulate the expression of chemokines in FLS, we found that monosodium urate crystals were able to significantly increase the release of the chemokine CXCL8 from both control FLS and RA-FLS (P,0.05). Combined treatment of monosodium urate crystals with TNF-a or IL-1b resulted in the synergistic production of CXCL8 from control FLS (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, there was no functional evaluation of this potentially important finding. However, there is now a study from KOBYASHI et al [47] suggesting that isolated human blood eosinophils harvested from healthy volunteers can release IL-17A protein, albeit in response to crystals of monosodium, a stimulus of unclear relevance for human asthma.…”
Section: Multiple Cellular Sourcesmentioning
confidence: 99%
“…These effects occur through Ca 2+ mobilization [19,194,195]. ATP can either interact directly with P2X ion channels or indirectly activate [196] IL-6 and IL-8 [197] by P2Y 2 receptor stimulation, while P2X1, P2X7, and P2Y 6 receptors might also be implicated in the release of IL-8 [196]. The P2Y 2 receptor subtype expressed on eosinophils is also suggested to be implicated in eosinophil chemotaxis [141,193].…”
Section: B and T Cellsmentioning
confidence: 99%
“…Also endothelial P2Y 2 receptors can affect eosinophil migration by regulating the expression of endothelial VCAM-1 which mediates migration and adhesion of eosinophils via the α4β1 integrin [193]. Monosodium urate (MSU) crystals induce the release of autocrine ATP from eosinophils which provides a pivotal positive feedback signal via P2 receptors on eosinophils [197]. DAMP damage-associated molecular patterns, PAMP pathogen-associated molecular patterns, VCAM-1 vascular cell adhesion molecule 1.…”
Section: B and T Cellsmentioning
confidence: 99%
See 1 more Smart Citation